Gaya Kepemimpinan Transformasional, Pengembangan Karir, Keseimbangan Kehidupan Kerja Terhadap Kepuasan Kerja Pegawai - Ardiansyah, Fandi; Andriani, Dewi; Kusuma, Kumara Adji (Politeknik Piksi Ganesha Indonesia, 2024)
There is an imbalance of work and personal life for employees so they experience stress and pressure which makes their morale decrease and employees feel pressured to the assigned tasks. So this study aims to identify Transformational Leadership Style, Career Development, and Work-Life Balance on Employee Job Satisfaction at Perumdam Mojopahit Mojokerto. This research uses quantitative techniques through a descriptive approach. The sampling technique uses total sampling, namely the sample members are taken as a whole. The type of data is primary data obtained through distributing questionnaires involving 125 employees at Perumdam Mojopahit Mojokerto. The results of this study indicate that transformational leadership style, career development, and work-life balance have a positive and significant effect on employee job satisfaction at Perumdam Mojopahit Mojokerto.